Effect of heat treatments on failure mechanism of SiCp/2124 Al composite - Murato?lu, M. (My University, 2005)
The mechanical response of a 17% (volume fraction) silicon carbide particles reinforced 2124 Al composite prepared by powder metallurgy techniques was studied by altering the matrix strength with different heat treatments. The fracture mechanisms and the deformation microstructure were examined by scanning electron microscopy. The results show that matrix strength appears to play an important role in influencing the behaviour of the composite under hardness and tensile loading conditions and also fracture mechanisms. The high matrix strength results in a larger decrease in yield strength due to the increasing damage probability. The tensile yield strength values decrease under peak aged and overaged condition whereas under the solutized condition the opposite effect can be seen.
Keywords: Fracture; Heat treatment; Metal matrix composites; Microstructure